Student society information system (SSIS) / Lee Ying Keng - Lee , Ying Keng (2001)
This is a project proposal report of the WXES3181 subject and a project report of the WXES3182 subject, taken by the final year student of Faculty of Computer Science and Information Technology (FSKTM). It is a delineation of intended project describing the proposed idea supported by a literature survey, its plan and· design. The system to be developed by the author is a web-based system intends to manage and store the information of the society in the University Malaya, besides providing society information such as society and activity list on the Internet. The software knowledge used to develop the system covers the Microsoft Visual Interdev6, ASP2.0, SQL Server Database7.0, Internet Information Server5.0 and so on. The main user of the system is the HEP's staff that responsible to the society information management. The system enables the FSKTM management level to keep track the society information and its activities. Since this system will display information through Internet, its information will be viewed by all of the students and then they will gain the benefit from it. The on-line's user who need that information also get advantages from the system. The current system used to manage the society information is carried on manually and most information is documented in paper. The current system faces a problem that the effectiveness of keeping track the society information and the smoothness of retrieving information is not satisfied enough. Pursuing the trend of moving forward to the office automation and paperless era, the computerization of the society information management will enable the process carried out in a more smoothly, effectively, efficiently and economically way. Hopefully the system will contribute to the achievement of the E-Faculty and E-University.